1996
DOI: 10.1002/eji.1830260835
|View full text |Cite
|
Sign up to set email alerts
|

Antigen processing and presentation of a naturally glycosylated protein elicits major histocompatibility complex class II‐restricted, carbohydrate‐specific T cells

Abstract: Antigen processing and presentation of a naturally glycosylated protein elicits major histocompatibility complex class 11-restricted, carbohydrate-specific T cellsIt is well known that T cells recognize antigen as processed peptides bound to major histocompatibility complex molecules on the surface of antigenpresenting cells. Recently, it has been shown that T cells can specifically recognize synthetic glycopeptides. However, whether glycopeptides are selected for presentation during antigen processing of glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…This T cell determinant contains lysine residues at position 264 and 270, which can become posttranslationally modified by hydroxylation and further galactosylated and glucosylated, creating many different epitopes containing hydroxyl, mono-and disaccharide groups in both RA and CIA. We have previously shown that autoreactive T cells predominantly recognize this epitope when it is posttranslationally modified at positions 264 and 270 by hydroxylation and further glycosylation [11][12][13]. The dominant T cell epitope is the side-chain of lysine at position 264 (K264) when the peptide is bound to A q , but when bound to DR4 the T cells recognize either position K264 or K270, although position 264 seems to be the more dominant of the two in this case.…”
Section: Introductionmentioning
confidence: 94%
“…This T cell determinant contains lysine residues at position 264 and 270, which can become posttranslationally modified by hydroxylation and further galactosylated and glucosylated, creating many different epitopes containing hydroxyl, mono-and disaccharide groups in both RA and CIA. We have previously shown that autoreactive T cells predominantly recognize this epitope when it is posttranslationally modified at positions 264 and 270 by hydroxylation and further glycosylation [11][12][13]. The dominant T cell epitope is the side-chain of lysine at position 264 (K264) when the peptide is bound to A q , but when bound to DR4 the T cells recognize either position K264 or K270, although position 264 seems to be the more dominant of the two in this case.…”
Section: Introductionmentioning
confidence: 94%
“…We used an established system with mouse hybridoma T cells and spleen-derived antigen-presenting cells (APCs). HCQ10 T hybridoma cells (18), which recognize the immunodominant CII peptide bound to the class II molecule H2-A q , or APCs were treated with PBS or with 4 mM GSH to increase the number of cell surface ϪSH groups. Higher numbers of cell surface thiols on T cells were shown to increase IL-2 production, whereas a higher number of thiol groups on APCs did not (Fig.…”
Section: Increasing the Number Of Cell Surface ؊Sh Groups On T Cells mentioning
confidence: 99%
“…We have previously shown the importance of galactosylation at position K 264 of CII259-273 for the immune recognition [12][13][14][15][16][17] and that CII in the healthy individuals is completely glycosylated at this position [16]. In line with these findings, an additional modification at position Q 267 by deamidation makes the study of the immune response more complex.…”
Section: Discussionmentioning
confidence: 54%
“…It is well established that during aging, inflammation, trauma or other pathologic processes, the frequency of posttranslational modifications, such as glycosylation, glycation, citrullination, oxidation, deamidation/transamidation or phosphorylation, is increased [10,11]. The role of glycosylated immunodominant CII260-270-peptide for development of autoimmune arthritis has been previously described [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation